A Study on Job Demands-Resources in the Public Sector - Tri Ongko Bayu Sadewo; Nourma Mei Shinta (Jurnal Organisasi dan Manajemen, 2024)
Purpose – This study aims to find out the effect of job demands, workload, job resources, autonomy, relevance, and competence, and personal resources, psychological capital in influencing job engagement, as well as testing the mediating role of burnout in public sector employees. Methodology – Respondents in this study were 201 employees of the Fiscal Policy Agency, using proportionate stratified sampling. The data was analyzed using Structural Equation Modeling with AMOS. Findings – The research showed that workload has a positive influence on burnout, while psychological capital, autonomy, and relatedness have negative influences on burnout. It is also demonstrated that psychological capital and relatedness have positive influences on job engagement, while burnout has a negative influence on job engagement. It cannot be proven that competence has a negative influence on burnout and a positive influence on job engagement. It was also found that burnout can mediate the relationship between workload, psychological capital, autonomy, and relatedness to job engagement. Still, it cannot mediate the relationship between competence and job engagement. Originality – Studies related to job demand resources in the public sector are very limited and are mostly conducted in the healthcare sector. This research also considered the conditions of the Covid-19 pandemic.